Parallel Assessment Tracks for Human-Centered Design (PATH): A Framework for Transitioning to a New Health Information Technology System. (September 2021) - Saleem, Jason J.; Maddox, Kyle; Herout, Jennifer; Ruark, Kurt
This practice-oriented paper presents a human-centered design (HCD) framework that we developed to perform a comprehensive evaluation of a new health information technology (HIT) system under development, intended to replace a legacy system. The Department of Veterans Affairs (VA) Veteran Crisis Line (VCL) program provides a vital service in crisis intervention and suicide prevention. VCL staff rely on a Customer Relationship Management (CRM) legacy system, Medora. VCL intended to replace Medora with Microsoft Dynamics 365 (D365) CRM system. Due to wide-spread criticism of D365, the VA Human Factors Engineering (HFE) team engaged in a multi-study, mixed-method HCD evaluation to investigate the legacy system and intended replacement in terms of ability to support VCL staff needs. The HCD framework we developed to perform this evaluation may be adapted for other large-scale HIT transitions and may provide human factors practitioners with guidance to make evidence-based decisions to support (or abandon) such transitions.